Ultrasonographic assessment of the renal size using a kidney length to vertebral body length ratio in cats - Martinez, Miryam; Soler, Marta; Laredo, Francisco G.; Belda, Eliseo; Agut, Amalia (Frontiers in Veterinary Science, 2022)
Ultrasonographic assessment of the renal size can provide useful clinical information, in combination with other ultrasonographic parameters. The aims of this study were to establish the agreement between the ultrasonographic and radiographic measurements of the kidneys (K) and vertebral bodies (L5 and L6), to establish an ultrasonographic measurement of kidney-to-vertebral body (L5 and L6) ratio to estimate the renal size in cats, and to assess the impact of age, body weight, sex, and gonadal status on the ultrasonographic measurements of the kidneys, vertebral bodies, and ratios. The vertebral bodies of L5 and L6 were chosen as they were easy to identify with ultrasonography (US) using the lumbosacral junction as a landmark, and they are not usually affected by vertebral anomalies. A total of 60 cats (19 intact males, 12 neutered males, 17 intact females, and 12 neutered females) were included in the study. The cats were divided into three age groups (<7 months, 7 months−7 years, and >7 years), two body weight categories (≤ 3.5 kg and >3.5 kg), and two sex and gonadal status groups (male and female, and intact and neutered, respectively). Measurements of the renal and vertebral body length were performed on the radiographic and ultrasonographic images. Two different ratios were obtained, namely, K/L5 and K/L6. There was no significant difference between the length of both kidneys and the length of the vertebral bodies of L5 and L6 on ultrasonographic or radiographic images. There was a good agreement between ultrasonographic and radiographic measurements of both kidneys and vertebral bodies. In conclusion, the kidney length to L6 length ratio obtained was 1.81 ± 0.20 (1.76–1.86), which was useful for evaluating the size of the feline kidney and was not influenced by the age, body weight, sex, or gonadal status.